The Analysis Study of Histopathologic Diagnosis of Metastatic Basal Cell Carcinoma of Skin: A Comprehensive Systematic Review - Prastyo, Wahyu Agus; Nugraheni, Artha Investari; Ayuningrum, Mutia Ruliana (The International Journal of Medical Science and Health Research, 2024)
Background: Metastatic basal cell carcinoma (MBCC) occurs at an exceedingly low rate, with an estimated incidence of 0.0028%, or 28 cases per 1,000,000 BCC diagnoses. The biological mechanisms underlying the metastatic potential of BCC remain poorly understood. This systematic review aims to evaluate the histopathologic features of MBCC based on literatures of the last 10 years. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. It excluded editorials, reviews from the same journal, and submissions without a DOI. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Result: Initially retrieving 360 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: Histopathologic diagnosis of metastatic basal cell carcinoma is crucial for determining tumor type, assessment of invasion depth, examination of excised margins, and identification of lymphovascular or perineural invasion. Molecular analysis can reveal mutations influencing tumor behavior and treatment resistance.